Eksistensi dan Dinamika Surau Sebagai Lembaga Pendidikan Islam di Indonesia Pra-Abad 20 - Hasna Izzatun Nawa; Sari, Intan Mulia Sari; Sutrimo Purnomo (Jurnal Bintang Pendidikan Indonesia, 2026)
Surau is the oldest traditional Islamic educational institution in Minangkabau and played an important role in the development of Islamic education in Indonesia before the twentieth century. This study is motivated by the modern shift in understanding the function of surau, which is often viewed merely as a place of worship, whereas historically it possessed broader educational, social, and cultural functions. The research aims to analyze the origins and transformation of surau, identify the roles of influential figures in its development, and examine its social functions within Minangkabau society. This study employs a qualitative approach using the historical research method through library research based on various primary and secondary sources. Data analysis was conducted through the stages of heuristics, source criticism, interpretation, and historiography to produce a systematic and factual historical account. The findings reveal that surau transformed from a Hindu-Buddhist ritual center into an Islamic educational institution that functioned as a center for religious instruction, character building, intellectual development, and social integration. Figures such as Syekh Burhanuddin Ulakan, Tuanku Nan Tuo, and Syekh Muhammad Djamil Djambek made significant contributions to the reform and development of the surau educational system. In addition, surau also served as a center for community deliberation, a residence for young men, and a space for moral and cultural development. The study implies that surau became an important foundation in shaping the Islamic educational system in the Nusantara by harmoniously integrating religious values, local culture, and social life.